ANALISIS PENGARUH KEKAYAAN PEMERINTAH DAERAH TERHADAP KEPATUHAN INTERNET FINANCIAL REPORTING (IFR) DENGAN LOKASI GEOGRAFIS SEBAGAI VARIABEL MODERASI - Rizqi Maulidan Prasetyo Aji; Mutiara Tresna Parasetya (Diponegoro Journal of Accounting, 2026)
This study examines how the financial condition of local governments influences compliance in presenting financial reports via the Internet, with the geographical features of the region acting as a moderating variable. This study aims to analyze the effect of local government wealth on Internet Financial Reporting (IFR) compliance with geographical location as a moderating variable. The study used financial report data and websites from 528 local governments in Indonesia that met the research criteria during the period January–April 2026, using a purposive sampling technique. Hypothesis testing was conducted using multiple logistic regression analysis with the help of SPSS 26.0. Based on the results of the study, simultaneously the variables of local government wealth, geographical location, moderating variables, type of local government, and size of local government influence Internet Financial Reporting (IFR) compliance. However, partially only the type of local government has a significant effect on IFR, while local government wealth, geographical location, size of local government, and the interaction of moderation do not show a significant effect.